Exploring how lifestyle weight management programmes for children are commissioned and evaluated in England: a mixed methodology study. Issue 12 (16th December 2019) - Mears, Ruth; Jago, Russ; Sharp, Deborah; Patel, Anamica; Kipping, Ruth; Shield, Julian P H
Abstract : Objective: To assess how lifestyle weight management programmes for children aged 4–16 years in England are commissioned and evaluated at the local level. Design: This was a mixed-methods study comprising an online survey and semistructured telephone interviews. Setting: An online survey was sent to all local authorities (LAs) in England regarding lifestyle weight management services commissioned for children aged 4–16 years. Online survey data were collected between February and May 2016 and based on services commissioned between April 2014 and March 2015. Semistructured telephone interviews with LA staff across England were conducted between April and June 2016. Participants: Commissioners or service providers working within the public health department of LAs. Main outcome measures: The online survey collected information on the evidence base, costs, reach, service usage and evaluation of child lifestyle weight management services. The telephone interviews explored the nature of child weight management contracts commissioned by LAs, the type of outcome data collected and whether these data were shared with other LAs or organisations, the challenges faced by these services, and the perceived 'markers of success' for a programme. Results: The online survey showed that none of the participating LAs was aware of any peer-reviewed evidence supporting the effectiveness of their specific commissioned service. Despite this, the telephone interviews revealed that there was no national formal sharing of data to enable oversight of the effectiveness of commissioned services across LAs in England to help inform future commissioning decisions. Challenges with long-term data collection, service engagement, funding and the pressure to reduce the prevalence of obesity were frequently mentioned. Conclusions: Robust, independent, cost-effectiveness analyses of obesity strategies are needed to determine the appropriate allocation of funding to lifestyle weight management treatment services, population-level preventative approaches or development of whole system approaches by an LA.